The State as Employer and the Civil Service - Frankel, S.J. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1963)
SummaryIn this paper, the author deals with the civil service rather than the public service. The two terms are not mutually exclusive, nor is the difference between them always clear. But a distinction can and should be made from the standpoint of employer-employee relations.